2020
DOI: 10.3390/sym12010163
|View full text |Cite
|
Sign up to set email alerts
|

On Neutrosophic Extended Triplet LA-hypergroups and Strong Pure LA-semihypergroups

Abstract: We introduce the notions of neutrosophic extended triplet LA-semihypergroup, neutrosophic extended triplet LA-hypergroup, which can reflect some symmetry of hyperoperation and discuss the relationships among them and regular LA-semihypergroups, LA-hypergroups, regular LA-hypergroups. In particular, we introduce the notion of strong pure neutrosophic extended triplet LA-semihypergroup, get some special properties of it and prove the construction theorem about it under the condition of asymmetry. The examples in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Hu, F. Smarandache and X.H. Zhang studied the properties and construction methods of an SP-NET-LA-semihypergroup and found that the symmetry of this algebraic structure is not perfect (see [23]). In addition, there are some related studies (see [24][25][26][27][28][29][30][31]).…”
Section: Introductionmentioning
confidence: 99%
“…Hu, F. Smarandache and X.H. Zhang studied the properties and construction methods of an SP-NET-LA-semihypergroup and found that the symmetry of this algebraic structure is not perfect (see [23]). In addition, there are some related studies (see [24][25][26][27][28][29][30][31]).…”
Section: Introductionmentioning
confidence: 99%